Highly Stable Trimers Formed by Human Immunodeficiency Virus Type 1 Envelope Glycoproteins Fused with the Trimeric Motif of T4 Bacteriophage Fibritin - Yang, Xinzhen (American Society for Microbiology, 2002)
The envelope glycoproteins of human immunodeficiency virus type 1 (HIV-1) function as a trimer composed of three gp120 exterior glycoproteins and three gp41 transmembrane proteins. Soluble gp140 glycoproteins composed of the uncleaved ectodomains of gp120 and gp41 form unstable, heterogeneous oligomers, but soluble gp140 trimers can be stabilized by fusion with a C-terminal, trimeric GCN4 motif (X. Yang et al., J. Virol. 74:5716-5725, 2000). To understand the influence of the C-terminal trimerization domain on the properties of soluble HIV-1 envelope glycoprotein trimers, uncleaved, soluble gp140 glycoproteins were stabilized by fusion with another trimeric motif derived from T4 bacteriophage fibritin. The fibritin construct was more stable to heat and reducing conditions than the GCN4 construct. Both GCN4- and fibritin-stabilized soluble gp140 glycoproteins exhibited patterns of neutralizing and nonneutralizing antibody binding expected for the functional envelope glycoprotein spike. Of note, two potently neutralizing antibodies, immunoglobulin G1b12 and 2G12, exhibited the greatest recognition of the stabilized, soluble trimers, relative to recognition of the gp120 monomer. The observed similarities between the GCN4 and fibritin constructs indicate that the HIV-1 envelope glycoprotein ectodomains dictate many of the antigenic and structural features of these fusion proteins. The melting temperatures and ligand recognition properties of the GCN4- and fibritin-stabilized soluble gp140 glycoproteins suggest that these molecules assume conformations distinct from that of the fusion-active, six-helix bundle.